2014
DOI: 10.1111/jav.00359
|View full text |Cite
|
Sign up to set email alerts
|

The origin of feather holes: a word of caution

Abstract: Antagonistic processes between parasites and their hosts are hallmarks of evolutionary ecology. A group of parasites is adapted to feed on feather keratin. In doing so, they inflict a variety of costs on avian hosts by causing feathers to degrade faster. Feather holes represent a class of feather damage that is attributed to the chewing bites of Phthirapteran lice. Consequently, hole counts were used as an approximation of lice infestation intensity when studying bird–lice interaction. Here, I express some res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…3 in Jenni-Eiermann et al, 2015), but they did not report the formation of fault bars. Although fault bars and pale bands are both feather malformations, they appear to have different proximal causes; thus, we advocate treating fault bars, feather holes, and pale bands as different phenomena (Pap et al, 2007;Vágási, 2014), while we encourage studying them simultaneously.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…3 in Jenni-Eiermann et al, 2015), but they did not report the formation of fault bars. Although fault bars and pale bands are both feather malformations, they appear to have different proximal causes; thus, we advocate treating fault bars, feather holes, and pale bands as different phenomena (Pap et al, 2007;Vágási, 2014), while we encourage studying them simultaneously.…”
Section: Introductionmentioning
confidence: 97%
“…A recent review convincingly suggested that feather holes 0.5-1 mm in diameter (also called 'fault spots' by Murphy et al, 1989) may be related to fault bars (Vágási, 2014). Previously, these holes were attributed to chewing lice (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…), whereas feather holes are small defects (diameter 0.5–1 mm) of the vane (Vas et al . , Vágási ). Feather structural damage could decrease flight feather quality and/or create asymmetry in the wing and tail.…”
mentioning
confidence: 99%
“…Feathers are inert integumentary appendages of birds that wear down and break gradually under natural conditions and are then replaced during moult (Vágási et al . , Vágási ). Physical abrasion, which primarily results from the impact of airborne particles and contact with different objects in the environment (Barrowclough & Sibley , Burtt , Bonser ), as well as from parasites such as feather lice, is thought to cause holes in feathers, though this conclusion is still controversial (Pap et al .…”
mentioning
confidence: 99%
“…, Vas et al . , Vágási ). Feather‐degrading bacteria have only relatively recently received attention as causitive agents resulting in feather abrasion, primarily as a consequence of the seminal work of Burtt and Ichida ().…”
mentioning
confidence: 99%